Advancement trends in dye-doped polymer dispersed liquid crystals—a survey review. (3rd May 2017) - Ahmad, Farzana; Jamil, Muhammad; Jeon, Young Jae
ABSTRACT: At present there is significant interest in the doping of various types of dyes into polymer dispersed liquid crystals (PDLCs) in display films. Till to date, various types of dyes have been employed to improve the electro-optical properties of PDLC films in various situations by different research groups. Some of the advantageous features of dye-doped PDLC predict that such dye-doping into the PDLC films resolve the scattering effect, improve the films absorbance, enhance the degree of alignment, stability, and the electro-optical properties of the film such as reflectance, contrast ratio and better transmittance. The current article contains a short review on the present and past studies conducted on the dye-doped polymers dispersed liquid crystals films. The fabrication techniques and their various applications in the different display areas are reviewed, along with the new key findings are discussed.